2012
DOI: 10.1021/ic3004245
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Bifunctional Zinc(II) Macrocyclic Complex Recognition of Thymine Bulges in DNA

Abstract: The zinc(II) complex of 1-(4-quinoylyl)methyl-1,4,7,10-tetraazacyclododecane (cy4q) binds selectively to thymine bulges in DNA and to a uracil bulge in RNA. Binding constants are in the low-micromolar range for thymine bulges in the stems of hairpins, for a thymine bulge in a DNA duplex, and for a uracil bulge in an RNA hairpin. Binding studies of Zn(cy4q) to a series of hairpins containing thymine bulges with different flanking bases showed that the complex had a moderate selectivity for thymine bulges with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 67 publications
1
71
0
Order By: Relevance
“…[6][7][8] In view of the importance of bulges in biological systems, compounds capable of targeting bulged sequences could be used as valuable probes for studying their role in nucleic acid function or could even have significant therapeutic potential. [10][11][12][13][14][15] Recently, we have demonstrated that DNA duplexes containing bulges are specifically recognized by [Fe 2 (I) 3 ]Cl 4 (I = C 25 H 20 N 4 ) metallosupramolecular helicates (Fig. The most promising bulge binding agents discovered to date are: those based on NCS-chrom, a wedge-shaped enediyne antitumor antibiotic neocarzinostatin chromophore, 2-acylamino-1,8-naphthyridine, rhodium intercalators or the zinc(II) complex of 1-(4-quinoylyl)methyl-1,4,7,10-tetraazacyclododecane, and dinuclear ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In view of the importance of bulges in biological systems, compounds capable of targeting bulged sequences could be used as valuable probes for studying their role in nucleic acid function or could even have significant therapeutic potential. [10][11][12][13][14][15] Recently, we have demonstrated that DNA duplexes containing bulges are specifically recognized by [Fe 2 (I) 3 ]Cl 4 (I = C 25 H 20 N 4 ) metallosupramolecular helicates (Fig. The most promising bulge binding agents discovered to date are: those based on NCS-chrom, a wedge-shaped enediyne antitumor antibiotic neocarzinostatin chromophore, 2-acylamino-1,8-naphthyridine, rhodium intercalators or the zinc(II) complex of 1-(4-quinoylyl)methyl-1,4,7,10-tetraazacyclododecane, and dinuclear ruthenium complexes.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempts have been made to prepare such compounds. Examples of promising bulge-binding agents discovered to date are: those based on NCSchrom, a wedge-shaped enediyne antitumor antibiotic neocarzinostatin chromophore, 2-acylamino-1,8-naphthyridine, rhodium intercalators, the zinc(II) complex of 1-(4-quinoylyl)methyl-1,4,7,10-tetraazacyclododecane, and dinuclear ruthenium complexes [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In recent reports, the loop regions have been essential for the binding of certain metal complexes, specifically Zn 2+ , where they interact with the thymidines within the loop region rather than with the G-tetrad. 5860 We hypothesize that the loop regions are also important for recognition by the Ru(II) dppz complexes by either preventing binding to the G-tetrad or by shielding the phenazine nitrogens. Seq27 lacks loops, whereas Seq28–Seq30 each have 3 loop regions (see Figure 7).…”
Section: Resultsmentioning
confidence: 99%